Invariant Natural Killer T Cells Shape the Gut Microbiota and Regulate Neutrophil Recruitment and Function During Intestinal Inflammation - Shen, Sj; Prame Kumar, Kathryn; Stanley, Dragana; Moore, Robert J.; Van, Thi Thu Hao; Wen, Shu Wen; Hickey, Michael J.; Wong, Connie H. Y. (Frontiers in Immunology, 2018)
Invariant natural killer T (iNKT) cells and neutrophils play an increasingly important part in the pathogenesis of inflammatory diseases, but their precise roles in modulating colitis remain unclear. Previous studies have shown important interplays between host immune system and the gut microbiota, and the resulting modulation of inflammation. However, the interactions between iNKT cells, neutrophil and gut microbiota in regulating colitis pathology are poorly understood. Here, we show iNKT cell-deficient Jα18-/- mice display reduced dextran sodium sulphate (DSS)-induced colonic inflammation compared to their wildtype (WT) counterparts. We reveal that there is a distinct gut microbiota shaped by the absence of iNKT cells, which comprises of microorganisms that are associated with protection from colonic inflammation. Additionally, the reduced inflammation in Jα18-/- mice was correlated with increased expressions of neutrophil chemoattractant (Cxcl1 and Cxcl2) and increased neutrophil recruitment. However, these neutrophils were recruited to the colon at day 3 of our model, prior to observable clinical signs at day 5. Further analysis shows that these neutrophils, primed by the microbiota shaped by the lack of iNKT cells, exhibit anti-inflammatory and immune-modulatory properties. Indeed, depletion of neutrophils in DSS-treated Jα18-/- mice demonstrates that neutrophils confer an anti-colitogenic effect in the absence of iNKT cells. Thus, our data supports a changing dogma that neutrophils possess important regulatory roles in inflammation and highlights the complexity of the iNKT cell-microbiota-neutrophil axis in regulating colonic inflammation.